PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) KOTA PEKANBARU 2012-2017 - Alexsander Yandra (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
The region authority to controlling the development planning contained in a regulations No. 25 of 2014 about the system of development planning. The regulation give an opportunity to the public to become involved in every process of development especially in the long-term process, medium-term although short-term. Medium-term development plan (RPJMD) become the important ones to every region especially Peknbaru city, because this formula was an elaboration of the vision and mission of regional head (Walikota) as well as executives products that directly related to the policies of city government development. As part of the process of formulating the development plan, the discussion of development planning (musrenbang) was the only step where the public get the chance to participate. Through a descriptive qualitative approach by the ethic data analysis and emic, concluded that the public participate in the discussion of development planning RPJMD of Pekanbaru city fully initiated by the government of Pekanbaru city, there was nothing mobilitation from the government to the public in musrenbang because the public voluntary attendance for the invitation, participation from the formal way and group and also there was nothing informal way, so this participation has not been effective because the public were not involved from the start in the formulations of the RPJMD, so that the public still seen as a subject in the development planning.